Autoantibodies in Systemic Lupus: Quite a Lot or Just a Few? - Migliorini, Paola; Anzilotti, Consuelo; Caponi, Laura; Pratesi, Federico; Rocchi, Valeria (Current Rheumatology Reviews, 2005)
Systemic lupus erythematosus (SLE) is characterized by the presence of a wide variety of autoantibodies directed against nuclear, cytoplasmic and cell membrane autoantigens. Several lines of evidence, however, suggest that the variety of autoantibodies in SLE may be more limited than was previously thought; different studies clearly suggest that lupus autoantibodies are able to bind multiple antigens. Cross-reactivity, i.e. the ability to bind multiple antigens with high affinity, is not limited to a single autoantibody specificity, but instead seems to be a general property of lupus autoantibodies, distinguishing them from immunization-induced antibodies. Many studies on cross-reactivity have focused on the autoantibodies present exclusively in SLE, and which are therefore considered to be markers of the disease, such as anti-dsDNA, anti-Sm and anti-ribosomal P protein antibodies. However, cross-reactivity has also been shown to be a feature of SLE autoantibodies that are not strictly disease-specific. The structural basis of cross-reactivity is not always clear. It may be due to the presence of common epitopes on different antigens, or to the specific structure of the antigen binding site that can then accommodate different epitopes. Whether one or more mechanisms of cross-reactivity are involved, the ability of an antibody to bind different antigens directly affects its pathogenic potential.
Keywords: cross-reactivity